Can LMWH improve the outcome of patients with inoperable stage III non-small cell lung cancer? - Kucukoner, Mehmet; Isikdogan, Abdurrahman; Kaplan, Muhammed Ali; Inal, Ali; Burhanedtin Zincircioglu, Seyit; Cit, Murtaza; Cil, Timucin; Karadayi, Bilgehan; Dirier, Ahmet; Yildiz, Ismail (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: Lung cancer is the most common malignancy, accounting for one-third of all deaths from cancer. Some studies have shown that low molecular weight heparin (LMWH) significantly prolongs the survival of patients with non-small cell lung cancer (NSCLC). The aim of this study was to determine the effects of treating inoperable stage III NSCLC with LMWH in addition to concurrent chemoradiotherapy. Material and methods : Eighty-two patients with inoperable stage III NSCLC were evaluated at Dicle University’s Medical Oncology Department between 2005 and 2010. All patients were treated with concurrent chemoradiotherapy (CRT) with or without LMWH (enoxaparin 4000 IU/day) depending on the patient’s risk of thrombosis. The primary objectives were to determine disease-free survival (DFS) and overall survival (OS) for patients treated with LMWH. Results : A total of 38 patients in the LMWH negative group and 44 patients in the LMWH positive group were included in the study. The median OS was 11.2 months for the enoxaparin recipients and 12.7 months for the non-enoxaparin group (p = 0.4). The median DFS was 9.3 months with CRT alone and 10.0 months with CRT plus enoxaparin (p = 0.9). The one-year OS rates were 47% and 34% for groups treated with CRT and enoxaparin plus CRT, respectively, while the two-year OS rates were 23% and 21%, respectively. No significant difference was noted between the two groups in terms of grade 3–4 hematologic toxicity and mucositis (p = 0.3). Conclusions: This study did not demonstrate improvements in survival for patients with NSCLC treated with enoxaparin. LMWH’s positive contribution is still controversial.